(untitled) (Aporte Santiaguino, 2020)
Ecuador in 1972 transformed its agricultural economy to one dependent on oil export earnings. However, a decrease is expected, exacerbated by a higher extraction energy cost. The energy rate of return (EROI), implies that the lower its value, the lower the net energy in favor of society. The methodology based on the David Murphy protocol was used as methodology. The objective of this investigation is to carry out a preliminary calculation of the EROI of Ecuadorian oil, at the country level and by blocks, obtaining preliminary EROI results for Blocks 7, 10, 15, 16, 21, 46, 47, 56, 57, 60, 61, 62 and 67, and from Ecuador. It is verified that the EROI decreases from a 43 : 1 to 27 : 1 ratio in twelve years, according to the API density and the percentage of BSW of the extracted crude oil that is higher. It is concluded that Ecuador, invests more and more resources, especially fuel for electricity generation, in twelve years increased by 65 %.